The gap between what'ought'to be and what students want - Mayer, Claude-Hélène (2010)
There’s no curriculum! There’s no curriculum!” The young man in the focus group was so frustrated that he had to repeat himself, not just once, but several times. I had just asked the group what their feelings were about their second-year coursework. His sentiments were echoed by many of the students in the group, all of whom had passed the rigorous application process into second year at Rhodes University’s School of Journalism and Media Studies.